The University in Crisis: Why (Neoliberal) Diversity Is Not the Answer - Bourabain, Dounia (Politics of the Low Countries, 2025)
The academic profession is often perceived as the epitome of meritocracy, while Critical Diversity and University scholars have demonstrated how it continues to grapple with gender and racial inequality across all levels. This article delves into the challenges of inequality in academia, particularly in the context of Belgian universities, and proposes a transformative approach to address these issues. Based on my previous work, I discuss how Diversity, Equality, and Inclusion (DEI) policies are misused and serve as a smokescreen to achieve the neoliberal interests of universities while remaining largely non-performative. Even more, EDI policies are introduced to bypass power, rather than change the power structures that continue to reproduce gender and racial inequality in academia. Using a praxis of hope, I move beyond identifying the problem by proposing the ‘University of the Common’ as an alternative academic system that goes beyond superficial diversity, aiming to create a university founded on social justice and in service of the common good. Key features include decolonizing knowledge, promoting antiracist feminist governance, and fostering a collective effort by academics to build an equitable university.